INTEGRASI TEKNOLOGI INFORMASI DAN KOMUNIKASI SEBAGAI MANFAAT PEMBELAJARAN PAI ABAD 21 DI MADRASAH DAN SEKOLAH - Sela Sopiana; Agus Pahrudin; Agus Jatmiko; Koderi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of Information and Communication Technology (ICT) in the 21st century has brought significant changes to the educational landscape, including the teaching of Islamic Religious Education (PAI) in madrasahs and schools. The integration of ICT enables the learning process to become more effective, creative, collaborative, and relevant to the needs of students in the digital era. This study aims to analyze the role, utilization, and integration of ICT in 21st-century PAI learning through a literature review of various scientific journals and academic sources. The findings show that ICT contributes to improving the quality of PAI learning by providing broad access to information, diverse learning media, enhanced learning motivation, and the strengthening of 4C competencies. Furthermore, the integration of ICT in Islamic education must remain grounded in the values of the Qur’an and Hadith to ensure that learning is not only cognitive but also shapes the character and spirituality of students. This study highlights the importance of teacher readiness, infrastructure, and educational management in optimizing ICT integration to create meaningful and high-quality PAI learning.